2019
DOI: 10.1371/journal.pone.0223195
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the fasciae to sex hormone levels: Modulation of collagen-I, collagen-III and fibrillin production

Abstract: Although it is now recognized that women suffer from myofascial pain to a greater extent than men, and that the muscular fasciae can respond to hormonal stimuli, thanks to the expression of sex hormone receptors, how the fasciae can modify their structure under hormonal stimulation is not clear. In this work, an immunocytochemical analysis of collagen-I, collagen-III and fibrillin were carried out on fibroblasts isolated from human fascia lata after in vitro treatment with various levels of sex hormones β-estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
3
21
0
2
Order By: Relevance
“…A deep analysis of biochemical characteristics and possible functions of the material contained in the HA-rich vesicles is a task for future investigations. However, this work demonstrated that fascial cells respond to the endocannabinoid system, regulating and remodeling the formation of the extracellular matrix (ECM), as already demonstrated for other types of stimuli, such as changes in hormonal levels [21]. The increase of the secreted hyaluronan can cause a greater, at least temporary, fluidity of the tissue, thanks to the role of the HA in facilitating the gliding between the fascial layers within and underlying the deep fascia during movement [22].…”
Section: Discussionmentioning
confidence: 52%
“…A deep analysis of biochemical characteristics and possible functions of the material contained in the HA-rich vesicles is a task for future investigations. However, this work demonstrated that fascial cells respond to the endocannabinoid system, regulating and remodeling the formation of the extracellular matrix (ECM), as already demonstrated for other types of stimuli, such as changes in hormonal levels [21]. The increase of the secreted hyaluronan can cause a greater, at least temporary, fluidity of the tissue, thanks to the role of the HA in facilitating the gliding between the fascial layers within and underlying the deep fascia during movement [22].…”
Section: Discussionmentioning
confidence: 52%
“…In our study, we used the Sirius Red assay, which does not distinguish between type I and III collagen production [23]. Nevertheless, one may speculate that the preferential coupling of adenosine A 2A receptor activation to the EPAC pathway in HSCF is more likely to increase the proportion of type III over type I collagen, as detected in the granulation tissue and immature scars, where the local concentrations of adenine nucleotides and adenosine are elevated [24,48]. This hypothesis is corroborated by the fact that high intracellular cyclic AMP levels achieved by inhibiting the cyclic AMP specific type IV phosphodiesterase with rolipram mimicked the pro-fibrotic role of A 2A receptors activation with CGS21680 or the adenosine precursor, AMP.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous in vitro study demonstrated that fascial cells can modulate the production of some components of the extracellular matrix according to hormone levels [ 16 ]. Therefore, hormone levels, together with biomechanical and delivery factors, could modify the morphology of abdominal muscles and fasciae [ 17 , 18 ]. We found a statistically significant dissymmetry of RA in VA women and of IO in CS women, which leads us to believe that the cause of this muscular dissymmetry is pregnancy itself and/or delivery.…”
Section: Discussionmentioning
confidence: 99%